APPLICATION OF LEARNING CHILD CHILD USING MACROMEDIA FLASH MX. - Meiliana Anggraini; Yuce Yuliani, SKom, MMSI (Jurnal Sistem Informasi, 2005)
The development of information technology on computer education causes more and more important, especially in children. Currently children are expected to be familiar with computers from an early age.  The appearance of interactive multimedia technology capable of presenting text, images, animations and video simultaneously or bergantiian. Children are increasingly familiar with the computer and make children more familiar with computers.  Multimedia applications which presents images such as for example in the form of animated Flash MX can provide or can produce an interactive application.